Optimal Design Configuration Using HOMER. (2016) - Kumar, Prashant; Pukale, Rahaul; Kumabhar, Nilesh; Patil, Utkarsh
Abstract: Target of the paper is to presents an idea about to design, simulation and analysis of stand-alone hybrid renewable energy resources for a typical ATM machine in remote locations. The main task of this paper is to give optimal solution to solve the problems of energy crisis in the globe. In current scenario the non-renewable sources are available in plenty amount to full fill our increasing demand. Considering the above information we have made an effort to analyze advantage of Distributed Generation considering solar power or wind power, alone can fluctuate, when connected together they provide reliable source of energy as diesel generator is used as backup unit for emergency. So the combination of these two forms of energy source with diesel generator provides reliable generation to provide a constant source of energy flow for the designed system. The main motive of this paper is to study feasibility of solar-wind-diesel hybrid power system with maximize the use of non-conventional generation system while minimizing the total system cost.